Right to a healthful environment: flagship of fundamental human rights – an international perspective - Ansari, Abdul Haseeb; Yogamalar, Sri (2015)

(untitled)
The right to a healthful environment gained global recognition with the growing trend in environmental consciousness and development of human awareness over the past decades. This human right is interlinked to our environment because an ecosystem which is otherwise will affect all living organisms to the very root of their existence. It is said that the right to a healthful environment is the flagship of all fundamental human rights. This stems from the indubitable fact that the survival of mankind is totally dependent on a clean, healthy and pollution-free environment. This paper delves into the constitutions of 23 nations in 6 different continents, with the right to a healthful environment as the central theme. It also explores the status, adequacy and enforcement of this basic human right as a constitutional right. To what extent Mother Nature is protected and how effective our environmental safeguards are, directly and indirectly, have reciprocal effects on the sustainable development of a country. In the midst of facing today’s global environmental challenges, it is the fervent hope of every citizen to live a decent life with reasonable living conditions for survival, and preservation of human dignity and sanity. This can only be achieved if the greed of the developed countries gradually erodes in the face of abating the sufferings of mankind by having a heart for humanity. Going back to basics, the right to a healthful environment actually relates to the sustainable survival of the humankind because it encompasses fresh air to breathe, safe and clean drinking water, sufficient nutritious food, proper homes for shelter and adequate sanitation facilities for the sustenance of all biota. Without securing and maintaining a healthful environment for present and future generations to come, mankind will drastically be deprived from enjoying the fundamental human rights that make life worth living.